Exceptional selling : how the best connect and win in high stakes sales / Jeff Thull - Thull, Jeff
"This is the first book to apply powerful diagnostic principles directly to sales conversations. It shows you how to create a customer engagement in which the common barriers to success - limited access, ambiguous words, objections, and cutthroat negotiations - melt away."--BOOK JACKET